2016
DOI: 10.20870/oeno-one.2016.50.1.53
|View full text |Cite
|
Sign up to set email alerts
|

A sensory, chemical and consumer study of the peppery typicality of French gamay wines from cool-climate vineyards

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: Within the protected designation of origin (PDO) Côtes d’Auvergne, Gamay N wines express unique peppery notes that may reflect high levels of rotundone. We investigated the typicality of these wines by determining their sensory, chemical and consumer profiles.</p><p style="text-align: justify;"><strong>Methods and results</strong>: Twenty-one Gamay N wines from the 2013 vintage from four French wine-growing areas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This opposition of appreciation between young (18–24 years) and older (>55 years) consumers is particularly marked for the 100 ng/L series, a common level of rotundone concentration found in Duras wine. In accordance with previous studies conducted on Gamay wines (Geffroy et al ), these findings suggest that winemakers should promote moderate to significant levels of rotundone in their Duras wine unless the product is specifically targeted to young consumers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This opposition of appreciation between young (18–24 years) and older (>55 years) consumers is particularly marked for the 100 ng/L series, a common level of rotundone concentration found in Duras wine. In accordance with previous studies conducted on Gamay wines (Geffroy et al ), these findings suggest that winemakers should promote moderate to significant levels of rotundone in their Duras wine unless the product is specifically targeted to young consumers.…”
Section: Discussionsupporting
confidence: 91%
“…Shiraz). Up to now, it has been identified in a wide range of grape cultivars including Pinot Noir, Durif, Graciano and Riesling (Herderich et al ), Duras (Geffroy et al ), Gamay (Geffroy et al ), Malbec and Abouriou (Cullere et al ) and Vespolina, Schioppettino and Grüner Veltliner (Caputi et al ). Recent research showed that two key polymorphisms in a newly discovered allele of the V. vinifera TPS24 gene were responsible for the production of α‐guaiene (Drew et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been identified in Pinot Noir, Durif, Graciano, Riesling (Herderich et al, 2012) and more recently in other cultivars such as Duras (Geffroy et al, 2014), Gamay (Geffroy et al, 2016), and Malbec, Abouriou (Cullere et al, 2016) grown in France under cool or Atlantic climate conditions. Differences in rotundone concentrations in wines made from four Duras certified clones suggest that rotundone was involved in the vine's natural response to powdery mildew attacks (Geffroy et al, 2015b).…”
Section: Introductionmentioning
confidence: 97%
“…In addition to Fer, IBMP has been identified in cultivars mainly from the Carmenets group such as Sauvignon, Cabernet Sauvignon, Merlot and Cabernet Franc (Allen et al, 1995;Hashizume and Umeda 1996). Rotundone has been found in in a wide range of varieties, including Pinot Noir, Durif, Graciano and Riesling (Herderich et al, 2012), Duras (Geffroy et al, 2014), Gamay (Geffroy et al, 2016a), Malbec and Abouriou (Cullere et al, 2016) and Vespolina, Schioppettino and Grüner Veltliner (Caputi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%